The Influence of Mimicry on the Reduction of Infra-Humanization - Szuster, Anna; Wojnarowska, Agnieszka (Frontiers in Psychology, 2016)
The paper investigates the role of mimicry in the reduction of infra-humanization. Mimicry as an automatic imitation of a partner’s behavior (this is known as “social glue”) connects people (Miles, Griffiths, Richardson and Macrae, 2010). Empirical findings have confirmed that mimicry leads to favorable treatment of the mimicker (van Baaren, Holland, Steenaert and van Knippenberg, 2003). The mechanism is reciprocal: the mimicker is more positively inclined towards the person mimicked (Chartrand and Bargh, 1999). Mimicry increases the sense of interpersonal closeness, reciprocal similarity, and facilitates the flow of interaction and helping behavior (Stel, van Baaren, and Vonk, 2008). At the same time, results point to a spontaneous inhibition of mimicry in the contact with members of negatively stereotyped groups (Bourgeois and Hess, 2008). So than, there are reasons to believe that purposeful activation of mimicry may reduce manifestations of negative attitudes towards others, i.e. infra-humanization. It was expected that imitating a model shown on video would lower the level of infra humanization, i.e. perceiving another individual as less capable than the Self of experiencing exclusively human (secondary) emotions. The study sample consisted of 117 female students. The study followed an experimental design and was conducted individually. It employed questionnaires and a purpose-made video recording showing a model whose facial expressions were to be mimicked by the participants. The results confirmed the predictions. Mimicking facial expressions reduced the level of infra-humanization compared to the no mimicking and control conditions [F (2, 114) = 3.39, p = 0.037, η2 = 0.06].